Studies on the detoxification of "kayos" (Dioscocea hispida Denst.) flour - Mones, Josefina (University of the Philippines in the Visayas, 1987)
Two samples of flour were prepared from "kayos" slices: one sample detoxified by washing with seawater and another detoxified by washing with fresh water from the faucet. These samples were analyzed for moisture, ash and alkaloid content. Mean values of the moisture and ash contents were compared. The lengths of detoxification were also compared. Results obtained showed that the moisture contents were the same. However, the ash content of the flour detoxified by fresh water and the difference was significant as shown by the result of the t-test on the significance of differences, The result of the qualitative test on the presence of alkaloid showed that there was a difference of 30 minutes for complete detoxification when seawater and fresh water were used.